From community building to governing strangers: reconceptualizing institutional relationships among governments, community organizations, and individuals - Sinclair, Thomas A. (2002)
Community building, with its emphasis on developing capacities of organizations in low-income communities, is sparking wide interest among public administration practitioners and scholars. However, the community-building literature oversimplifies the complex relationships between individuals community institutions, and government. Using a structuration approach theorized by Giddens, these interactions are explored using the arrival of new residents - or strangers - as the impetus for community redefinition. The article concludes that all types of communities, not just those typically targeted for community building may benefit from governmental interventions when undergoing transitions. - Reproduced.
Keywords: Public administration